Based on laser energy absorption ratio differential algorithm methane concentration detection system - Liang, Fang; Xun, Yanqin; Wu, Wenyi; Fu, Jianmei (Frontiers in Physics, 2023)
To reduce the interference of other gases and improve the detection accuracy in CH4 concentration detection, a CH4 concentration detection system is proposed, and a ratio differential algorithm is designed. The difference value of the absorbed light intensity between chamber 1 and chamber 2 used to suppress the calculation of CH4 concentration by other component gases. The high concentration of CH4 gas in chamber 3 used to obtain the accurate position of the characteristic absorption peak, and it is applied as a boundary condition for data extraction in chamber 1. Two sets of gases chamber differential calculations were used, one set was used to calculate the differential value of laser energy at the characteristic position of CH4 absorption, and the other set was used to calculate the differential value of laser energy for the other gases. Then, calculate the proportion coefficients of the two sets of difference values to obtain the CH4 concentration inversion function using this structure. The interfering gases include C2H6, SO2 and CO2. A total of 1000 sets for sample data were collected for the mixed gas, with 400 sets as the sample data and the rest as the test samples. The results show that the accuracy of CH4 concentration inversion by this algorithm is about 3 times that of traditional algorithm. The algorithm modeling time is approximately 1/4 of that of traditional methods. It has certain advantages in detecting CH4 concentration in environments with interfering gases.